Peran Media Audio-Visual dalam Pembelajaran IPAS di Sekolah Dasar - Nizfa Khairiyah; Affi Fatu Rahmi; Adrias Adrias; Salmaini Safitri Syam (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
The lack of understanding and interest of students in learning Social Studies (IPS) at the elementary school level is often caused by a monotonous and less varied teaching approach. This situation makes students feel bored, have difficulty in understanding the material, and are less actively involved in the learning process. To overcome this, audio-visual media emerges as an interesting alternative in creating a more interactive learning experience. This research aims to examine the role of audio-visual media in social studies learning in elementary schools. It discusses the benefits of audio-visual media in improving learners' understanding, the challenges that may be faced when using this media, and the strategies that can be applied to make its utilization more effective. This type of research uses a literature study approach to explore the contribution of audio-visual media in social studies subjects. The results indicate that the use of audio-visual media, such as learning videos, animations and interactive presentations, has a positive influence on students' learning outcomes. This media is able to convey information in a clear, interesting and easy-to-understand manner, thus significantly increasing learners' interest and understanding.